Irrigation application efficiency and uniformity of water distribution using multi-outlet pipe and resource conservation technologies - Rajurkar, G.B.; Patel, N.; Natarajan, Rajmohan; Rajput, T.B.S.; Prathapar, Sanmugam A.; Varghese, C. (2016)
Irrigation experiments were conducted during November to April under wheat crop in the winter season of 2012-13 and 2013-14 in the farmer’s field at Galibkhedi village located in Karnal District, Haryana State, India. In the study, collapsible multi-outlet pipe (MOP) along with single outlets pipe (SOP) was tested in farmer’s field under wheat cultivation. Irrigation was carried out in five treatments including tillage (T) with SOP and MOP; zero-tillage (ZT) with SOP and MOP, and furrow irrigation with raised bed (FIRB). Iso-time profile of waterfront spreading and advance indicated that irrigation water distribution was uniform under the plot irrigated using MOP as compared to plot irrigated using SOP. In addition, water distribution was uniform under zero tilled plots as compared to tilled plot. Results implied that MOP has several advantages over SOP in terms of application efficiency (AE) and uniformity of water distribution. Average application efficiency for the first study year was found to be in the order of ZT-MOP (82.41%) > FIRB (76.79%) > ZT-SOP (75.25%) > T-MOP (74.85%) > T-SOP (69.79%). Average application efficien-cy for the second study year was found to be in the same order as first year with some deviation in values. In the second year values of mean application efficiencies were ZT-MOP (82.58%) > FIRB (77.13%) > ZT-SOP (73.04%) > T-MOP (69.65%) > T-SOP (66.13%). Overall, this study concludes that irrigation under wheat crop using collapsible multi-outlet pipe (MOP) with zero tillage practices is a suitable option for surface irrigation that accomplishes uniform distribution of water with higher application efficiency.